Content and Language Integrated Learning in Castilla-La Mancha, Spain: Exploring Pedagogical Practices and Experiences through Classroom Observations - Rani, Devika; Inamdar, Neeta (Issues and Ideas in Education, 2022)
Background: Content and Language Integrated Learning (CLIL) is a European innovative interdisciplinary educational convergence that intends to promote multilingual competence among students through the learning of the subjects in a second/foreign language. This approach is considered one of the significant developments in the field of education. Purpose: A research study was designed with the objective of exploring and understanding the nature and method of CLIL practices prevalent in bilingual primary and secondary school classrooms in Castilla La Mancha, Spain. Spain was chosen because it is one of the pioneering countries that steered an exhaustive variety of research and experiments in CLIL practices in its diverse educational contexts. Methods: Adopting qualitative research method Participant Classroom Observations, twenty classes of two bilingual schools--fifteen classes of Natural Science and Social Science in primary school and five classes of Music at Secondary School that used CLIL approach were observed and findings recorded using observation template. Results: The findings provided a myriad view of the bilingual experiences in the classrooms, diversity and range of pedagogical practices used, student teacher interaction dynamics present, positive learning environment provided for the students in the classes to mention a few. Conclusion: The study concludes with the understanding of the 'added value' and the numerous benefits the approach provides for the students. As a fresh and innovative approach, CLIL promotes holistic and meaningful learning catering to the needs of twenty first century education systems.